THE IMPLEMENTATION OF APPROXIMATIVE SYSTEM OF ENGLISH FOREIGN LANGUAGE IN SPEAKING SKILL - Abdillah Abdillah Abdillah (UIN Sumatera Utara, 2017)
The objective of this research was to find out the improvement of the students ability in speaking skill English foreign language by implementation approximative system. The research conductied by using classroom action research. The subject of this study was students of eleventh grade. The class consisted of 30 students. The data were taken from the students score, observation sheet, diary notes and documentation. Based on the speaking tests, the students’ score kept improvement in every test, it could be seen from the improvement of students’ mean score from pre – test, post test of cycle I and post test cycle II. In the pre-test, students who got up 65 there were 5 of 30 students (16.66%). In the post-test of cycle I, Students who got up 65 there were 25 of 30 (83.33%). It means that there was improvement 66.67%. In the post-test of cycle II, students who got up 65 there were 29 of 30 students (96.66%). The improvement was about 13.33 %. The total improvement of the students score pre-test to post-test of cycle II was 80%. The improvement also can be proved by the result of observation sheet and diary notes, it showed that the expressions of the result of observation sheet and diary notes, it showed that the expressions of the students, they more active, enthusiastic, brave, confidence to respond and comprehend the text in learning process. Therefore, it was found that teaching speaking of English foreign language by implementation of approximative system could improve the students’ ability in speaking skill.